"I need to love and to be loved”: perspective of young adults with hearing loss in Kabul-Afghanistan - Amarkhail, Freba; Ibrahimkhil, Fahima; Sidek, Suriati (Stichting Liliane Fonds, 2021)
Purpose: This research aimed to explore love and belonging or social needs, of young adults with hearing loss in Kabul, Afghanistan. Method: A qualitative research method specifically, the phenomenological approach, was adopted to conduct this research. An in-depth semi-structured interview was used to interview ten participants. Conclusion: Overall, two themes and four sub-themes were derived from thematic analysis. The finding indicates that social support from family members and people in the surrounding, and a sense of belonging are fundamental social needs of people with hearing loss. Further research is needed to investigate the reasons behind the unmet social needs of people with hearing loss. Limitation: The major limitations of the study were - lack of official data regarding people with hearing disability in Afghanistan, non-availability of sign language interpreters, and cultural constraints faced by female study participants.